2017
DOI: 10.6061/clinics/2017(01)10
|View full text |Cite
|
Sign up to set email alerts
|

Omega-3 fatty acid supplementation as an adjunctive therapy in the treatment of chronic kidney disease: a meta-analysis

Abstract: The aim of this study was to evaluate the benefits and risks of omega-3 fatty acid supplementation in patients with chronic kidney disease. A systematic search of articles in PubMed, Embase, the Cochrane Library, and reference lists was performed to find relevant literature. All eligible studies assessed proteinuria, the serum creatinine clearance rate, the estimated glomerular filtration rate, or the occurrence of end-stage renal disease. Standard mean differences with 95% confidence intervals for continuous … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 28 publications
3
21
0
Order By: Relevance
“…In a study comparing patients with CKD progression compared to control patients, Afshinnia et al reported that CKD progression was associated with lower Cholesteryl ester (CE), diacylglycerols (DG), PC, plasmenylcholine (PC-P), PE-P, and phosphatidic acid (PA), and elevated PE and monoacylglycerols (MAG)(19). This finding suggests that patients with CKD progression with a decrease of longer acyl chains and polyunsaturated lipids might benefit from the effects of polyunsaturated fatty acid supplementation, as some previous studies have suggested(20,21). In our study, although both groups represent patients who had CKD progression, the SC group had higher PC and LPE than the AMR group and a trend for lower LPC suggesting that subpopulations with varying degrees of inflammatory milieu might exist with the CKD population.…”
Section: Discussionsupporting
confidence: 66%
“…In a study comparing patients with CKD progression compared to control patients, Afshinnia et al reported that CKD progression was associated with lower Cholesteryl ester (CE), diacylglycerols (DG), PC, plasmenylcholine (PC-P), PE-P, and phosphatidic acid (PA), and elevated PE and monoacylglycerols (MAG)(19). This finding suggests that patients with CKD progression with a decrease of longer acyl chains and polyunsaturated lipids might benefit from the effects of polyunsaturated fatty acid supplementation, as some previous studies have suggested(20,21). In our study, although both groups represent patients who had CKD progression, the SC group had higher PC and LPE than the AMR group and a trend for lower LPC suggesting that subpopulations with varying degrees of inflammatory milieu might exist with the CKD population.…”
Section: Discussionsupporting
confidence: 66%
“…Since then, 3 new studies were published including 344 patients (55% increases in sample size). Moreover, another meta-analysis on omega-3 fatty acid supplementation as adjunctive therapy in the treatment of chronic kidney disease by Jing et al [11] in 2017 suggested that omega-3 fatty acid supplementation is associated with a significantly reduced risk of end-stage renal disease and delays the progression of this disease, but in this study, diabetic patients were not included.…”
Section: Introductionmentioning
confidence: 89%
“…Long-chain omega-3 polyunsaturated fatty acids, including eicosapentaenoic acid (EPA) and docosahexaenoic acids (DHA), have shown anti-inflammatory, antithrombotic properties and benefits on kidney function [9][10][11]. There is a number of clinical trials studying in various types of kidney diseases including IgA nephropathy [12], lupus nephritis [13,14] and polycystic kidney disease [15].…”
Section: Introductionmentioning
confidence: 99%
“…Meta-analyses have been limited by the quality of available studies. To date, there is insufficient evidence to recommend the use of omega-3 fatty acids to prevent death, CV events or CKD progression both in pre-dialysis CKD and in ESKD patients [133][134][135]. The recent REDUCE-IT (Reduction of Cardiovascular Events with Icosapent Ethyl-Intervention Trial) supports a CV protective effect of EPA [136].…”
Section: Omega-3 Fatty Acidsmentioning
confidence: 99%